2004
DOI: 10.1590/s1516-89132004000100017
|View full text |Cite
|
Sign up to set email alerts
|

Tree species sprouting from root buds in a semideciduous forest affected by fires

Abstract: Tree species which sprouted from root buds were identified in a 3.6ha area of a Semideciduous Seasonal Forest fragment in Campinas, São Paulo State (22° 55' S and 47° 05' W)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 24 publications
3
37
0
19
Order By: Relevance
“…The spatial distribution of the C. sylvestris sprouts from roots pre-fire was in a random pattern, becoming clustered post-fire, according to both indices used (table 1). Sprouting from root buds could represent an effective strategy of spatial reoccupation and vegetative propagation; moreover, sprout shoots have the potential to emerge at variable distances from the main trunk and become independent plants (Rodrigues et al 2004). Imatomi et al (2009) reported that C. sylvestris seeds exhibit a low germination rate under laboratory conditions, whereas the presence of root buds may explain the wide distribution and high population density of this species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial distribution of the C. sylvestris sprouts from roots pre-fire was in a random pattern, becoming clustered post-fire, according to both indices used (table 1). Sprouting from root buds could represent an effective strategy of spatial reoccupation and vegetative propagation; moreover, sprout shoots have the potential to emerge at variable distances from the main trunk and become independent plants (Rodrigues et al 2004). Imatomi et al (2009) reported that C. sylvestris seeds exhibit a low germination rate under laboratory conditions, whereas the presence of root buds may explain the wide distribution and high population density of this species.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the spatial distribution pattern of C. sylvestris changed from random to clustered in response to the fire in the area. Some studies have shown that fire events damage plant aerial parts, causing a reduction in the amount of auxin reaching the roots, which in turn stimulates the development of sprouts (Bosela & Ewers 1997, Hoffmann & Moreira 2002, Rodrigues et al 2004. The sprouts from the roots may then lead to a clustered pattern, since the mean distance between a main trunk and its sprouts depends on the energy cost of root production and the presence of spots favorable to their growth (Hutchings 1997).…”
Section: Resultsmentioning
confidence: 99%
“…A importância da rebrota como estratégia de sobrevivência na regeneração pós-fogo é relatada para diferentes ecossistemas florestais tropicais (Uhl et al 1981, 1982, Kruger 1984b, Rouwn 1993, Marod et al 2002e Kennard et al 2002. em Floresta Estacional Semidecidual, estudos mostram que esta formação possui considerável número de espécies com capacidade de rebrota (Castelani & Stubblebine 1993, Hayashi et al 2001, Rodrigues et al 2004). Entretanto, a falta de informações obre os episódios de fogo, sobre a comunidade previamente existente, bem como a inexistência de monitoramento da vegetação em regeneração em longo prazo não permitem concluir sobre a importância do fogo como elemento de pressão evolutiva para a Floresta estacional semidecidual.…”
Section: Resultsunclassified
“…Podem ser citados Castelani & Stubblebine (1993), Penha et al (2002), Rodrigues et al (2004Rodrigues et al ( , 2005, Martins et al (2002) e silva et al (2005), cujas principais conclusões são de que a regeneração de fragmentos atingidos pelo fogo fica dificultada pela ocorrência das lianas e que as rebrotas constituem-se em importante estratégia das plantas para reocupação da área perturbada. Analisando as perdas decorrentes da passagem do fogo sobre o banco de sementes nesta formação florestal, Melo et al (2007) verificaram que o fogo ocasionou diminuição da densidade e da riqueza do banco de sementes, sendo maiores os impactos quanto menor a distância da borda da floresta.…”
Section: Introductionunclassified
“…O histórico de uso da área influencia fortemente o banco de sementes (Araújo et al 2001;Mônaco et al 2003; Auld e Denham 2006) e a rebrotação de indivíduos, a partir de caules e raízes (Fujisaka et al 1998;Rodrigues et al 2004), influenciando assim o estabelecimento das espécies no estágio inicial da sucessão e, as espécies estabelecidas podem determinar a composição florística nos estágios posteriores devido à competição por espaço, luz e nutrientes que ocorre durante o processo sucessional (Fujisaka et al 1998;Coelho et al 2003).…”
Section: Discussionunclassified